The Palgrave handbook of organizational change thinkers - Szabla, David B.; Pasmore, William A.; Barnes, Mary A.; Gipson, Asha N. (Palgrave Macmillan, 2017)
The key developments and advancements in organizational change over the last century are the result of the research, theories, and practices of seminal scholars in the field. While most books simply outline a theorist's model, this handbook provides invaluable insight into the contexts and motivations behind their contributions. Organized alphabetically, this handbook presents inspiring and thought-provoking profiles of prominent organizational change thinkers, capturing the professional background of each and highlighting their key insights, contributions, and legacy within the field of organizational change. By bringing these scholars' experiences to life, we can begin to understand the process of organizational change and analyze what remains to be done for organizations today. This book is the first of its kind--the go-to source for learning about the research and practice of organizational change from those who invented, built, and advanced the field. This comprehensive handbook will help researchers and students to develop their organizational change research agendas, and provide practitioners with concepts, theories, and models that can easily be applied to the workplace to lead change more effectively.
Keywords: Organizational change -- History.; Economics -- Sociological aspects.; elektronické knihy; electronic books